Morphological Characterization of Okra (Abelmoschus [Medik.]) Accessions - Ogwu, Matthew Chidozie; Onosigbere-Ohwo, Uruemu; Osawaru, Moses Edwin (UI Scholars Hub, 2018)
Okra (Abelmoschus [Medik.] species) is a prominent vegetable due to the diverse economic roles of its leaves, fruits, seeds, floral parts, and stems. This study investigated the morphological distinctiveness among varieties and between species of okra. Five okra accessions were obtained from the National Centre for Genetic Resources and Biotechnology, Nigeria, including two A. esculentus (NG/OA/03/12/157 and NG/OA/05/12/159) and three A. caillei (NG/OA/03/12/158,NG/SA/DEC/07/0475, and NG/SA/DEC/07/0482) species. During the developmental stage, the accessions exhibited adegree of similarity; however, at maturity, the leaf and fruit color, height, leaf shape, and flowers of the five accessionsbecame distinct. A cluster of the phenotype was observed at 4.123 level of coefficient of similaritywith two distinctclusters. Distinct morphological features included the nature of the epicalyx segment, the position of the fruit on thestem, fruit shape, and fruit color. These features may be used to identify the accessions. The common morphological features of clusters 1 and 3 were leaf shape and fruit length at maturity. Significant differences were observed among allthe five accessions in terms of stem length, petiole length, and leaf node. This study suggests that morphological variations exist among the accessions, which can be further enumerated through molecular characterization. The characteristics could distinguish the Abelmoschus accessions into A. caillei and A. esculentus and provide credence to the use of morphological characteristics to characterize plant genetic resources. These characteristics may be exploitedby plant breeders for sustainable utilization of the okra germplasm.